Expansão por umidade de revestimentos cerâmicos : métodos de medida e variáveis envolvidas - Nastri, Suelen (Universidade Federal de São Carlos, 2015)
The expansion by humidity (EPU) is characterized by the increase in the size of the ceramic body when in contact with water in liquid or vapor. The phenomenon can contribute to the development of severe pathologies in ceramic coatings such as glaze and cracking of detachment after installation of facades. The EPU has been studied since the early twentieth century, and the studies led to the creation of today's existing commonalities. However, there are still many divergences about the measurement procedures both as regards the measurement of expansion, as the accelerated hydration method used to predict the expansion ceramic materials may suffer over time. In this sense, through this research project, intended to contribute to the improvement of moisture expansion of evaluation methods in ceramic tiles, as well as identifying the main variables responsible for the EPU in ceramic tiles currently produced in the country. To carry out the project, samples were collected from different commercial ceramics, preferably used for the coating of external facades. The EPUs these samples were characterized by different procedures in the laboratory, to planned changes in the methods of hydration of the samples as well as methods of quantifying the expansions undergone. Simultaneously, the selected products were characterized microstructurally to identify the factors that determine susceptibility to moisture expansion. Both hydration and the method for measuring the dimensional change affect EPU values obtained, the latter was more predominant. The study of the reburn temperatures showed that it is not necessary to use temperatures higher than 350 ° C. Hydration time of the study shows a continuous increase in moisture expansion values. Microstructural analysis helps in understanding the EPU phenomenon.
Moisture expansion of ceramic tiles : measurement methods and variable involved
Keywords: Expansão por umidade; Revestimento cerâmico; Destacamento; ENGENHARIAS